Tuotekehitys, toimialojen panos-tuotosrakenteen muutokset ja talouden kasvu - Olavi Rantala (The Research Institute of the Finnish Economy (ETLA), 2003)
Tutkimuksessa arvioidaan tuotekehityksen vaikutuksia toimialojen ja koko talouden tuotantoon ja tuottavuuteen. Merkittävin ero aiempaan tutkimukseen on se, että tuotannon laadun paranemisen ja uusien tuotteiden kehittämisen kautta kanavoituvia tuotekehityksen vaikutuksia toimialojen tuotannon volyymin kasvuun arvioidaan toimialojen välituotekaupan riippuvuuksille estimoidusta muuttuvakertoimisesta panos-tuotosmallista. Estimointitulosten mukaan korkeaa teknologiaa edustava elektroniikkateollisuus erottuu muista toimialoista tuotekehityksen tehokkuudessa ja tuotannon laadun paraneminen voi selittää jopa puolet elektroniikkateollisuuden tuotannon kasvusta vuosina 1976-1999. Koko kansantalouden tuotannon kasvusta noin kolmannes on voinut olla peräisin tuotekehityksellä aikaansaadusta tuotannon laadun paranemisesta ja uusien tuotteiden kehittämisestä. Tuotekehityksen tuottavuusvaikutusten arvioinnissa merkittävin ero aiempaan tutkimukseen on tuotantoteknologian ja kokonaistuottavuuden kehityksen kytkeminen pääomakannan laadun paranemiseen. Tämän mahdollistaa tutkimuksessa toteutettu toimialojen tuotannon laatuindeksien sekä niihin pohjautuvien investointitavaroiden ja toimialojen pääomakannan laatuindeksien laskenta. Tuotantofunktion simulointitulosten perusteella tuotekehityksellä on pitkäaikaisia vaikutuksia tuottavuuteen. Tuotekehityksen voimakkain vaikutus tuotantoon sen laadun paranemisen kautta ajoittuu välittömästi tuotekehityspanostuksen lisäämisen jälkeiseen aikaan, mutta pääomakannan laadun paranemisen vauhti nopeutuu tuotekehitysmenojen pysyvän tasokorotuksen seurauksena jopa kymmenkunta vuotta, kunnes pääomakannan poistuma alkaa sitä vähitellen hidastaa. Tämä investointitavarateollisuuden tuotekehityksen lisääntymisen aikaansaama kokonaistuottavuusvaikutus on merkittävin sellaisilla matalan teknologian teollisuusaloilla, kuten metsäteollisuudessa, joiden oma tuotekehityspanostus kasvaa keskimääräistä hitaammin tai vaikuttaa tuotannon laatuun keskimääräistä vähemmän. – – This study evaluates the impact of R&D on the quality and volume of production in different sectors of the Finnish economy by applying a new approach based on an econometric variable coefficient input-output model. A basic hypothesis in the study is that changes in product quality in different sectors, induced by R&D inputs, may explain changes in the input-output structure of the economy. In the econometric estimation of the model the economy has been divided into nine different sectors based on their technology level and general importance in the Finnish economy. The estimation results show that R&D efforts have been most effective in the high technology electronics industry, where improvements in product quality explain about half of the output volume growth in the years 1976-1999. A third of the overall growth in the Finnish economy in this period may have resulted from improvements in product quality and the creation of new products achieved by increased R&D efforts. Traditionally, the effects of R&D on productivity have been assessed from an econometrically estimated production function specification where the R&D input has been inserted as an additional factor of production along with the capital and labour inputs. Using the sectoral product quality indices obtained from the estimation of the variable coefficient input-output model to compute quality indices for investment goods and, further, the capital stock by sector gives a new approach for modelling the improvement of technology and the growth of total factor productivity. In this case, the residual of the production function, which reflects total factor productivity, consists of two multiplicative components. The first component is the quality of the product of the sector, which is contained in the volume of output as measured in the National Accounts. The second component is production technology modelled as a power function of the quality of the capital stock of the sector. The estimation results based on CES and CD production function specifications indicate that lower technology industries, such as the forest industry, have utilised most effectively the improvement of the quality of capital stock in their production technology. Simulating the reaction of total factor productivity to a permanent simultaneous increase in real R&D inputs in all sectors indicates that product quality reacts immediately to an increase in R&D efforts, whereas production technology responds much more slowly because this can take place only gradually via the improvement of the quality of investment goods. In fact, production technology improves most rapidly some ten years after the increase in R&D expenditure level. This means that the impact of R&D inputs on productivity may be quite persistent in some industries, particularly in low technology industries.
Keywords: 330; T&k; panos-tuotosrakenne; tuotannon laatu; tuottavuus; R&D; input-output structure; product quality; productivity; Input-Output; Produktivität; Forschung; Produktqualität; Finnland